Farnesoid X receptor agonism protects against diabetic tubulopathy: Potential Add-On Therapy for diabetic nephropathy - Marquardt, Andi; Nawroth, Peter Paul (Journal of the American Society of Nephrology, 2017)
Visual Overview: Download figureOpen in new tabDownload powerpoint. Established therapies for diabetic nephropathy (dNP) delay but do not prevent its progression. The shortage of established therapies may reflect the inability to target the tubular compartment. The chemical chaperone tauroursodeoxycholic acid (TUDCA) ameliorates maladaptive endoplasmic reticulum (ER) stress signaling and experimental dNP. Additionally, TUDCA activates the farnesoid X receptor (FXR), which is highly expressed in tubular cells. We hypothesized that TUDCA ameliorates maladaptive ER signaling via FXR agonism specifically in tubular cells. Indeed, TUDCA induced expression of FXR-dependent genes (SOCS3 and DDAH1) in tubular cells but not in other renal cells. In vivo, TUDCA reduced glomerular and tubular injury in db/db and diabetic endothelial nitric oxide synthase-deficient mice. FXR inhibition with Z-guggulsterone or vivo-morpholino targeting of FXR diminished the ER-stabilizing and renoprotective effects of TUDCA. Notably, these in vivo approaches abolished tubular but not glomerular protection by TUDCA. Combined intervention with TUDCA and the angiotensin-converting enzyme inhibitor enalapril in 16-week-old db/db mice reduced albuminuria more efficiently than did either treatment alone. Although both therapies reduced glomerular damage, only TUDCA ameliorated tubular damage. Thus, interventions that specifically protect the tubular compartment in dNP, such as FXR agonism, may provide renoprotective effects on top of those achieved by inhibiting angiotensin-converting enzyme.